2015
DOI: 10.1002/2014jd022987
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of tropical tropospheric composition to lightning NOx production as determined by replay simulations with GEOS‐5

Abstract: The sensitivity of tropical tropospheric composition to the source strength of nitrogen oxides (NO x ) produced by lightning (LNO x ) is analyzed for September through November 2007 using the NASA GEOS-5 model constrained by MERRA fields, with full GMI stratospheric-tropospheric chemistry and an LNO x algorithm that is appropriate for use in a climate modeling setting; satellite retrievals from OMI, TES, and OMI/MLS; and in situ measurements from SHADOZ ozonesondes. Global mean LNO x production rates of 0 to 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 92 publications
4
54
0
Order By: Relevance
“…In Wild (2007) and Liaskos et al (2015) the ozone burden and mean tropospheric column ozone, respectively, scaled approximately linearly with increases in lightning emissions. Using the mean bias data in Table 1 we can calculate the mean increase in ozone column associated with each TgN emission from lightning.…”
Section: Global Annual Spatial and Temporal Ozone Distributionsmentioning
confidence: 99%
See 3 more Smart Citations
“…In Wild (2007) and Liaskos et al (2015) the ozone burden and mean tropospheric column ozone, respectively, scaled approximately linearly with increases in lightning emissions. Using the mean bias data in Table 1 we can calculate the mean increase in ozone column associated with each TgN emission from lightning.…”
Section: Global Annual Spatial and Temporal Ozone Distributionsmentioning
confidence: 99%
“…The solid line shows the mean annual tropopause as diagnosed using the modelled meteorology. Liaskos et al (2015) identified that, even with the same total global emissions, the magnitude and distribution of radiative forcing resulting from lightning emissions is dependent on the method for distributing the emissions horizontally and vertically. The changes in zonal-altitudinal distribution discussed in this section show that these changes could be expected as a result of changes in ozone in the upper troposphere.…”
Section: Differences In the Zonal-altitudinal Distributions Of O X Anmentioning
confidence: 99%
See 2 more Smart Citations
“…Hegglin and Shepherd, 2009;Zeng et al, 2010) and lightning-produced ozone (e.g. Liaskos et al, 2015).…”
Section: Precursor 30mentioning
confidence: 99%